Efficacy and toxicity of mitoxantrone and oral etoposide in the treatment of hormone-refractory prostate cancer: pilot study - Rafael Kaliks; Camila Guerra; Auro Del Giglio (Einstein (São Paulo), 2010)
ABSTRACT Objective: To evaluate the efficacy and toxicity of the association of mitoxantrone and oral etoposide. Methods: Twelve consecutive patients with metastatic hormone-refractory prostate cancer were treated with mitoxantrone and oral etoposide. Toxicity, response rate and response duration were assessed. Results: Partial response was observed in two patients (response duration of seven and four months) and one patient had stable disease (during four months). Mitoxantrone and oral Etoposide were well tolerated and did not affect tolerability to subsequent chemotherapy. Conclusion: Mitoxantrone and oral etoposide association is an active and well-tolerated regimen in hormone-refractory prostate cancer.